Enhanced Grain Refinement of W18Cr4V High‐Speed Steel Using in Situ TiN−Nb−Cr@Graphene/Fe Nanocomposite Inoculant. Issue 10 (3rd May 2021) - Bai, Lina; Cui, Chunxiang; Zhang, Jianjun; Zhao, Lichen; Zheng, Guixing; Cui, Sen
Abstract : Traditional cast W18Cr4V high‐speed steel (HSS) undergoes elemental segregation during solidification, which deteriorates its macroscopic mechanical properties. Previous reports have demonstrated that grain refinement overcomes this issue. Therefore, herein, the effect of an Fe‐based nanocomposite inoculant on carbide dispersion is investigated. The inoculant comprises graphene‐coated ceramic particles prepared in situ via mechanical grinding in a ball grinder, where material thermodynamics are considered. The microstructure of the inoculated W18Cr4V HSS is analyzed using transition electron microscopy, scanning electron microscopy, energy‐dispersive spectroscopy, and X‐ray diffraction. The orientation relationship among the phases is ( 200 ) NbC // ( 1 1 ¯ 1 ¯ ) Fe 3 W 3 C // ( 00 2 ¯ ) Fe 3 C . The nanocomposite ceramic particles serve as a base for the heterogeneous nucleation of Fe3 W3 C and Fe3 C, thereby increasing the nonuniform nucleation rate for enhanced grain refinement. This behavior plays a crucial role in the intragranular reinforcement of HSS. Abstract : The effect of Fe‐based nanocomposite inoculant on the microstructure of W18Cr4V is studied. The inoculant is composed of graphene‐coated ceramic nanoparticles prepared by mechanical ball milling. The results show that the matrix and carbide of W18Cr4V are significantly refined by this inoculant, and the mechanical properties of steel are significantly improved.